Izazovi i perspektive političkog vođstva u 21. vijeku / The Challenges and Perspectives of 21st Century Political Leadership - Pejanović, Mirko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
This text is the review of a book Ph.D. Tatjana Lazić Političko vođstvo: Teorije i iskustva u savremenim demokratijama (Political Leadership: Theories and Experiences in Contemporary Democracies), Sarajevo, Dobra knjiga, 2016.